"The Meaning of 'Meaning is Normative' ". (26th February 2012) - Fennell, John
Abstract This paper defends the thesis that meaning is intrinsically normative. Recent anti‐normativist objectors have distinguished two versions of the thesis – correctness and prescriptivity – and have attacked both. In the first two sections, I defend the thesis against each of these attacks; in the third section, I address two further, closely related, anti‐normativist arguments against the normativity thesis and, in the process, clarify its sense by distinguishing a universalist and a contextualist reading of it. I argue that the anti‐normativist position is successful only against the universalist reading but point out that normativists do not require this reading of the thesis; the contextualist one is both possible and desirable for them. Furthermore, I argue that anti‐normativists require the contextualist reading of the normativity thesis to make their case, as well as to avoid meaning relativism. In the final two sections of the paper, I explain how a contextualist understanding of the normativity thesis is compatible with Quine's elimination of analyticity, thus undermining a key underlying reason for anti‐normativism, and I respond to the objection that a contextualist reading of the normativity thesis is either self‐contradictory or else trivial.